Restoration, reconstruction, and revisionism: altering our virtual perception of damaged manuscripts - Craig-McFeely, J (De Gruyter, 2020)
The answers to questions about the boundaries of digital retrieval of damaged manuscript content are extremely fluid, dependent on ethical and aesthetic expectations and the intended end-use of the edited images. Digital intervention is currently the only way to restore the contents of many manuscripts to usability. The chapter examines the Forensic Reconstruction of damaged manuscript leaves through a combination of various digital and analog evidence; in particular, what is achievable, the ethical constraints and practical decisions informing the end result, and the palaeographical value of the outputs.